2018
DOI: 10.1002/hpm.2497
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health facility performance in Indonesia using the Pabón‐Lasso model and unit cost analysis of health services

Abstract: Total health care costs have dramatically increased in Indonesia, and health facilities consume the largest share of health resources. This study aims to provide a better understanding of the characteristics of the best-performing health facilities. We use 4 national Indonesian datasets for 2011 and analysed 200 hospitals and 95 health centres. We first apply the Pabón-Lasso model to assess the relative performance of health facilities in terms of bed occupancy rate and the number of admissions per bed; the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Similar to our findings, drugs and supplies constituted the highest proportion of costs of a 200-bed hospital in Myanmar, while in Bangladesh it constituted more than half of the unit costs for service delivery [5, 52]. On the other hand, at Indonesian hospitals and Indian primary and tertiary health facilities, personnel constituted the largest cost component [3, 39, 53]. These differences may be due to the costs of drugs and materials and staff remuneration being below the market rate for the Cambodian public sector [54].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to our findings, drugs and supplies constituted the highest proportion of costs of a 200-bed hospital in Myanmar, while in Bangladesh it constituted more than half of the unit costs for service delivery [5, 52]. On the other hand, at Indonesian hospitals and Indian primary and tertiary health facilities, personnel constituted the largest cost component [3, 39, 53]. These differences may be due to the costs of drugs and materials and staff remuneration being below the market rate for the Cambodian public sector [54].…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, this decision may improve the structural quality of hospitals and utilisation of services, as observed in India [43]. While noting that these types of facilities are considered efficient when bed occupancy rates are more than 80% [3, 39], the low rates observed at HCBs and the CPA1 hospital in this study suggest the need for caution in expanding or maintaining these types of health facilities.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Further, many literatures argued that poorer people appeared to be more frequently in illness and needed more healthcare services [36]. The findings could be attributable to the fact that public facilities were more utilized by deprived people than the wealthier ones, which facilitated service production compared to the hospitals with a lower proportion of poor people [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with results of three studies have been conducted in Iran, one in Tunisia, and one in Indonesia. 22,26,[37][38][39] In 2011, Sajadi and her colleagues have also revealed that the percentage of efficient hospitals in Iran in 2006 and 2007 was 45% and 43%, respectively, meanwhile Ajlouni and other researchers found that the efficiently performing hospitals in Jordan were 46.6%, and 60% for the same years. 40,41 Nevertheless, some other hospitals exhibited a lower performance when compared with Gazan hospitals in this study as only 15% and 24% were in zone 3.…”
Section: F I G U R Ementioning
confidence: 99%